Blood Supplement Tablet Consumption Behavior Among Female Adolescents At Vocational School X In Kubu District, Karangasem, Bali - Ni Komang Ekawati; Ni Kadek Indah Ratih Sharaswathi; Dinar Saurmauli Lubis; Desak Putu Yuli Kurniati; Komang Ayu Kartika Sari (Universitas Pahlawan Tuanku Tambusai, 2026)
The provision of blood supplement tablets is a program from the Ministry of Health that aims to improve the health of adolescent girls which is expected to minimize the incidence of anemia and increase iron content in the body. The implementation of the program at SMK X has reached 100%, which means it has reached the 2017 strategic plan target of 30% in the provision of TTD. However, the location is the place with the highest anemia rate in Karangasem Regency. The purpose of the study was to determine the consumption behavior of blood supplement tablets of adolescent girls of SMK X. The study used mixed methods. Data were collected through questionnaires given to all students, interviews with teachers and health center officers, and FGDs with selected adolescent girls. Data analysis was conducted by univariate analysis (quantitative) and thematic analysis (qualitative). The results showed that the TTD consumption behavior of female students at SMK X was mostly irregular (60%). The majority of schoolgirls' knowledge was in the good category (74.4%) and positive attitude (51.2%). Routine behavior of female students at SMK X was driven by feeling the benefits of TTD, complying with health center recommendations, positive beliefs, parental support, peer support, and health center support. Factors inhibiting informants from consuming TTD routinely were forgetting, fishy smell, rejecting body responses such as feeling nauseous and dizzy after consuming TTD, and negative beliefs. Consistent and strict supervision of TTD consumption and health promotion education on alternatives to consuming TTD are needed